The Influence of Boma Gunung Pasang Tourism on the Environment in Suci Village, Panti District - Istiqomah, Nailal; Ambarwati, Dewi; Fitriah, Haniatul (Aspirasi Masyarakat Intelektual Islam Nusantara, 2023)
The environment is a collection of physical conditions that include the state of natural resources. Forests play a vital role in life as a climatic counterbalance, a source of economic development, and a source of people's lives. Humans are social beings, thus it is anticipated that they understand environmental ethics in order to preserve environmental cleanliness, which is intimately tied to all human actions that cannot be separated from garbage or products that might contaminate the environment. This study employs data gathering methods such as observation, interviews, and documentation. The subject of this study is Boma tourism on Mount Pasang. According to the research findings, the environment may be utilized as a tourism destination by paying attention to environmental management so that the beauty of the environment is preserved. Boma tourism has a positive impact on Gunung Pasang Hamlet by raising people's knowledge of their environment. Additionally, the use of controlled trash may provide economic value, and the presence of Boma tourist attractions helps the community to create their own jobs.